Energy retrofit infill panels for historic timber-framed buildings in the UK: physical test panel monitoring versus hygrothermal simulation. (4th March 2021) - Whitman, Christopher J.; Prizeman, Oriel; Gwilliam, Julie; Shea, Andy; Walker, Pete
Abstract : As we aim to decarbonize the built environment, care must also be taken to minimize the negative impact of retrofit actions on historic buildings' fabric and cultural significance. Work to date in the UK has focused on the retrofit of historic solid masonry construction, with little research into historic timber-framed buildings. With these buildings, where infill panels are beyond repair or have previously been substituted with inappropriate materials, there exists the potential to retrofit panels with a higher thermal performance. The research presented in this article compares the monitoring of three physical test panels mounted between climate-controlled chambers with digital hygrothermal simulations in order to investigate the risk of increased moisture which may threaten the surrounding historic fabric. Results of previously unpublished cyclical testing are is also included. Whilst all prediction methods successfully identified interstitial condensation where measured, major discrepancies existed between simulated and measured results, and between different simulation methods.